Development of red/near-infrared fluorescent molecules and macromolecules for biomedical applications - Yang, Cangjie (2017)
Red/near infrared (R/NIR) fluorescence imaging based on organic materials has emerged as one of the most effective modalities in clinical practice due to the availability of biocompatible contrast agents, maneuverable instruments, and high spatial/temporal resolution with good sensitivity. To date, many organic fluorophores including organic small molecules and macromolecules have been developed as promising candidates for R/NIR bioimaging. However, the imaging efficacy of this technique has been limited by several challenges such as the lack of highly fluorescent R/NIR contrast agents, aggregation caused quenching (ACQ) effect, poor photostability, non-biodegradability and small Stokes shift. In this thesis, we have developed several strategies to overcome these challenges. One of the strategies is to precisely control the molecular packing of the structures to improve the optical properties of R/NIR fluorophores. Specifically, Chapter 2 presents a new crystallization-induced-emission (CIE) fluorophore (denoted as Indigoid-B). A transition from amorphous to crystalline state of Indigoid-B was induced upon ultrasonication, accompanied with an enhancement of red emission at 600 nm. In Chapter 3, the aggregated states (H-, J-aggregates) of NIR dye pyrrolopyrrole cyanines (PPcys) in colloidal nanoparticles were investigated by modification of chemical structure, variation of concentration and the treatment of ultrasonication. Nanoparticles containing J-aggregates of PPcy exhibited a narrow emission band at 773 nm, a fluorescent quantum yield comparable to that of indocyanine green. Another strategy of overcoming ACQ effect is developed in Chapter 4 and Chapter 5 by covalently conjugating biodegradable polycaprolactones (PCL) to red-emitting conjugated polymers (denoted as PFTB) and NIR dye PPcy. Two kinds of colloidal nanoparticles composed of PCL-grafted PFTB were prepared in the absence and presence of PCL-tethered PPcy, respectively. The presence of PCL-tethered PPcy enabled colloidal nanoparticles to emit at a longer wavelength through Förster resonance energy transfer (FRET). The introduction of PCL improved the quantum yields of both these two systems as compared to those without PCL, where FRET colloidal nanoparticles exhibited a NIR emission at 760 nm and a high quantum yield of 46%. A strong candidate for clinical theranostics also calls for the improvement in optical properties of R/NIR imaging agents. In Chapter 6, we developed a kind of theranostic unimolecular micelles by grafting amphiphilic block copolymers from conjugated polymers PFTB. The surrounding amphiphilic scaffold helped to suppress aggregation of the central PFTB fluorophore, resulting in a high quantum yield of 22%. The hydrophobic layer of side chain was used to physically entrap drugs for chemotherapy. To address the potential problem of drug leakage, we utilized amphiphilic random copolymers containing drug-modified units as side chain of conjugated polymers instead in Chapter 7. The experiments of in vivo bioimaging and therapy demonstrated a good tumor-specific ability and long retention time in tumor. Overall, this thesis has explored several ways to overcome the currently existing drawbacks of organic R/NIR fluorescent probes, especially aggregation caused quenching, non-degradability, small Stokes shifts, and further integrated the chemotherapy function with the R/NIR emitting unimolecular micelles for promising theranostic applications.